2005
DOI: 10.3349/ymj.2005.46.2.245
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ketorolac Injected via Patient Controlled Analgesia Postoperatively on Spinal Fusion

Abstract: Lumbar spinal fusions have been performed for spinal stability, pain relief and improved function in spinal stenosis, scoliosis, spinal fractures, infectious conditions and other lumbar spinal problems. The success of lumbar spinal fusion depends on multifactors, such as types of bone graft materials, levels and numbers of fusion, spinal instrumentation, electrical stimulation, smoking and some drugs such as nonsteroidal anti-inflammatory drugs (NSAIDs). From January 2000 to December 2001, 88 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
(27 reference statements)
0
40
0
Order By: Relevance
“…In one study of 88 patients, 30 of whom were given ketorolac after spinal fusion, the incidence of incomplete union or non-union was higher in those given ketorolac; the relative risk was approximately six times higher than control group of patients who did not receive an NSAID and smoking was said to have had no effect on the spinal fusion outcome (Park et al, 2005 Level III-2). In another study of 405 patients, 228 of whom were given ketorolac after similar surgery, there was no significant difference in the non-union rates between the two groups; in this study there were no patients who smoked (Pradhan et al, 2008 Level III-3).…”
Section: Bone Healingmentioning
confidence: 99%
“…In one study of 88 patients, 30 of whom were given ketorolac after spinal fusion, the incidence of incomplete union or non-union was higher in those given ketorolac; the relative risk was approximately six times higher than control group of patients who did not receive an NSAID and smoking was said to have had no effect on the spinal fusion outcome (Park et al, 2005 Level III-2). In another study of 405 patients, 228 of whom were given ketorolac after similar surgery, there was no significant difference in the non-union rates between the two groups; in this study there were no patients who smoked (Pradhan et al, 2008 Level III-3).…”
Section: Bone Healingmentioning
confidence: 99%
“…Confounding can mask the observed statistical association between treatment and outcome, either inflating the estimate or diminishing it. For example, in a study comparing opioid patient controlled analgesia with non-steroidal analgesia (NSAIDs) following lumbar fusion surgery, Park et al found that individuals infused with a combination of ketorolac and fentanyl were more likely to have delayed fusion than those using fentanyl alone, and concluded that NSAIDs were responsible for the delayed recovery [43]. However, in Park et al study, individuals using NSAIDs were far more likely to smoke cigarettes than those taking opioids.…”
Section: Randomized Controlled Trialmentioning
confidence: 82%
“…[20][21][22][23][24][25][26]28 Three studies were further excluded for the following reasons: (1) no detailed information about the dose of NSAIDs that those patients had received, 20 (2) patient population including not only nonunion but also infection or other reasons for reoperation, 22 (3) paper retracted by the journal 25 (Figure 1). In 1 study, 26 a group of patients who underwent the surgery by 1 surgeon before November 1989 (before the introduction of ketorolac) had a signifi cantly higher nonunion rate than the others without any detailed explanation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies involving animal models have documented evidence supporting this hypothesis. [15][16][17][18][19] And several clinical trials have also evaluated the effect of NSAIDs on spinal fusion, [20][21][22][23][24][25][26][27][28] but most of them included relatively small cohorts of patients and thus their results lacked statistical strength. The aim of this metaanalysis was to determine the effects of postoperative NSAIDs on spinal fusion.…”
mentioning
confidence: 99%